Landslide Analysis Using Seismic Refraction Tomography And MASW: a Case Study in Ponorogo, East Java, Indonesia - Yusri Prayitna; Widya Utama; Dwa Desa Warnan (Institut Teknologi Sepuluh Nopember, 2019)
Ponorogo district morphology form consisting of highlands and hills make this area vulnerable to landslides. Based on the BNPB (National Disaster Management Agency) data from 2013 to 2017, 77 landslides and 35% have occurred in Ngrayun and Slahung sub-districts. One area that has the potential to experience landslides is Tugurejo village in Slahung District. This study aims to determine the physical properties of subsurface rocks using SRT (Seismic Refraction Tomography) and MASW (Multi-channel Analysis of Surface Waves). The seismic velocity distribution defined from the SRT and MASW at the study sites shows a zone with a higher porosity that is interpreted to represent the level and depth of rock mass movement. P-wave velocity and S-wave indicates very low velocity of 500 – 1200 m/s and 100 – 250 m/s at depths up to 5 m.